BANKING STOCK ABNORMAL RETURN ANALYSIS OF PRE AND POST MERGER AND ACQUISITION IN INDONESIA - Rivanny Astricia; Isni Andriana; Reza Ghasarma (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2020)
The number of mergers and acquisitions (M&A) in Indonesia is growing because of government policy and also their usefulness as a corporate tool to pursue strategic growth and profit. This study aims to analyze the abnormal returns of banking industries pre and post-merger and acquisition in Indonesia. Using a sample of 7 M&A deals in Indonesia from 2018 to 2019, the event study methodology used in this study is Paired Sample T-Test to tell the difference between pre and post abnormal returns. The data that use for calculating is -30 until +30 of Merger and Acquisition. The result shows that from 7 mergers and acquisition there is only one bank that has a significant difference while the rest does not have a significant difference pre and post the event. This research hopefully can be used for further research, useful for investment practitioners.